Effect of sonication on teliospores of Tilletia indica - KAUR, SATVINDER (Indian Phytopathology, 2002)
Germination of teliospores of T. indica appeared to be 'criticaJly' conditioned by thick waJl layers which are required to be compromised prior to germination as occurs in nature. Similar effect can be achieved experimentally using drastic physical action of ultrasonic vibrations. This treatment helped in inducing more than 50 per cent germination in newly formed teliospores and up to 73 per cent in one year old ones. Excessive sonication, (higher doses and prolonged time of treatment), however, even killed the teliospores without affecting the germination of the wheat seed. This could be exploited for killing the Karnal bunt inoculum in wheat seed lots